Performance of reinforced concrete flat slab strengthened with CFRP for punching shear - Ghayeb H.H.; Atea R.S.; Al-Kannoon M.A.-A.; Lee F.W.; Wong L.S.; Mo K.H. (Elsevier Ltd, 2024)
Existing reinforced concrete (RC) slabs need punching shear reinforcement due to design defects, structural damage, increased loading, corroded reinforcement bars, and change in the use or function of the buildings. Strengthening methods such as using carbon fibre reinforced polymer (CFRP) sheets as external reinforcements in the tension area have proven to be useful in increasing the punching shear capacity and ductility of RC members. Therefore, this study aims to investigate the effect of using CFRP strengthening method in two-way RC slabs. Three strengthened RC solid flat slab samples in addition to unstrengthened slab samples were tested and subjected to static load to simulate the punching shear effect at the middle of the slab. Based on the test results, the samples strengthened with CFRP showed better performance in terms of delaying the appearance of the first crack, improving the resistance of shear crack propagation, and enhancing the load-displacement and ductility capacities compared to the control sample. In addition, the failure mode of the strengthened samples with CFRP was improved and the capacity for punching shear was increased. Furthermore, the analytical model to predict the ultimate punching shear strength has good agreement with the requirements of the practical codes, thus it can be used for the design and analysis of CFRP strengthened slab. 2022 The Authors